The History of the Ecological Poster Museum Creation at the Kharkiv State Academy of Design and Arts - Mudalige, Olena (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The article attempts to analyze in a chronological dimension (1991–2021) the history of creation and functioning of the International Triennial of Ecological Poster “4th Block”, the largest artistic and environmental action in Ukraine, aimed at drawing attention to environmental problems in the world and the spiritual and moral foundations of life. The features of each triennial are consistently reflected, the changes in time of the pictorial component of the modern poster as they move away from Chernobyl tragedy are traced, its artistic and communicative features and innovations used by designers to promote important universal human aspirations are identified. The basis of the study was the materials of albums-catalogs of eleven triennials held, the collection of graphics and posters itself, the book of memoirs of the founder of the triennial. Attention is focused on the natural process of transforming the collection of posters and graphics into a museum that can become the center of modern design culture. A special role of the Kharkiv State Academy of Design and Arts in the organization and support of the “4th Block – Museum, Archive, Laboratory” was noted. An institution of higher education with a powerful creative and scientific potential, its own traditions and original teaching methods, KSADА constantly organizes the educational process in such a way as to acquaint students with history and new trends in contemporary art, including graphic design. This approach attracts new generations of the artistic elite of Ukraine to participate in a dialogue between representatives of different cultural regions and broadcast their own artistic experience to the world space in order to spread the best ideas of mankind. The article presents the conclusions from this study and the prospects for further research in this direction.